Exploring bulk viscous unified scenarios with gravitational waves standard sirens. Issue 1 (14th January 2023) - Yang, Weiqiang; Pan, Supriya; Valentino, Eleonora Di; Escamilla-Rivera, Celia; Paliathanasis, Andronikos
ABSTRACT: We consider the unified bulk viscous scenarios and constrain them using the Cosmic Microwave Background observations from Planck 2018 and the Pantheon sample from Type Ia supernovae. Then we generate the luminosity distance measurements from ${\cal O}(10^3)$ mock Gravitational Wave Standard Sirens (GWSS) events for the proposed Einstein Telescope. We then combine these mock luminosity distance measurements from the GWSS with the current cosmological probes in order to forecast how the mock GWSS data could be effective in constraining these bulk viscous scenarios. Our results show that a non-zero time dependent bulk viscosity in the universe sector is strongly preferred by the current cosmological probes and will possibly be confirmed at many standard deviations by the future GWSS measurements. We further mention that the addition of GWSS data can significantly reduce the uncertainties of the key cosmological parameters obtained from the usual cosmological probes employed in this work.